Agent-Based Modeling and Simulation for Integrating Social and Natural Dynamics in Water Resources Management - Sousa, D.; Coelho, C.; Alves, C.; Ralha, C. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2024)
Water resources modelling based solely in natural dynamics may presented limitations due to neglection of social factors. This article presents an exploratory study of agent-based modeling and simulation for managing water use conflicts between farmers and regulators and among farmers. Water users’ behavior is guided by the Belief, Desire, and Intention (BDI) reasoning model, aiming at welfare, often through crop sales and income generation. Heterogeneous behavior is captured through diverse cooperation profiles linked to different compliance levels with water use rules set by the regulatory agent. The resulting framework offers insights into environmental flows and water consumption equity among users, testing opportunities for new water policies.